Effect of tibolone treatment on intima-media thickness and the resistive indices of the carotid arteries - (:unkn) unknown (My University, 2003)
OBJECTIVE: To assess the effect of tibolone treatment on the intima-media thickness (IMT) of the common carotid artery (CCA) and the resistive indices (RIs) of the CCA and internal (ICA) and external (ECA) carotid and the vertebral arteries (VAs) in postmenopausal women as sonographic markers of atherosclerosis. DESIGN: A prospective study. SETTING: University hospital. PATIENT(S): Twenty postmenopausal women who had no cardiovascular disease. INTERVENTION(S): Noninvasive measurements of the IMT of the CCA and the RI of the CCA, ICA, ECA, and VA were made with ultrasound at baseline and after 12 weeks of tibolone treatment. MAIN OUTCOME MEASURE(S): IMT of the CCA and RI of the CCA, ICA, ECA, and VA. RESULT(S): Three months of tibolone treatment decreased the IMT of the CCA (mean +/- SD) from 0.70 +/- 0.22 mm (95% confidence interval [CI], 0.60-0.80) to 0.47 +/- 0.17 mm (95% CI, 0.39-0.55) by 28%. Resistive indices of the CCA, ICA, and VA also decreased significantly. CONCLUSION(S): The present study showed that tibolone treatment decreases both the IMT of the CCA and RI of the CCA, ICA, and VA, which appears to be related to its anti-atherosclerotic effect. Nevertheless, the clinical implications of these findings are yet to be investigated.
Keywords: Adult; Female; Humans; Middle Aged; Ultrasonography; Biomarkers; Norpregnenes; Postmenopause; Prospective Studies; Arteriosclerosis; Carotid Arteries; Vascular Resistance; Tunica Media; Tunica Intima; Estrogen Receptor Modulators